Covid-19 and the 2020/21 International Moots Season - CHEN, Siyuan (Institutional Knowledge at Singapore Management University, 2021)
This is the seventh annual review of Singapore’s performance in international moot court competitions. While the previous season already felt the ravaging effects of the pandemic, it was more of the same this season, although this time round, all the major competitions were prepared to go online.